Beliefs about foreign language knowledge - Henshall, Ann (2012)
In today’s globalised world languages interact in ways that were not possible a century or even three decades ago. Within the last eight years the European Union has grown from 15 to 27 member countries, and this has added 12 working languages to it. Business has gone global with small companies now able to extend their reach beyond their national or traditional markets to new ones in any country on any continent. For such expansion communication is essential. In addition to these institutional and economic uses of languages, the Internet has made it possible for the private citizen from any part of the world to communicate face to face in real time with others as well as to post individual statements of positions about their life or beliefs via blogs, social networks etc. In such a changing world, language users are constantly adapting to and changing the way language and languages are used. In particular, young people today are at home with digital technology and use it creatively to interact with others. They are, in fact, the first generation to have grown up with it and have been called “digital natives”. It is therefore of interest to know what these young people think about language and the language(s) they are using. What beliefs and attitudes do they hold?